Building Confidence through Intrinsic Rewards: The ‘ASYIK’ Model in Early English Education - Malage, Gloria Risnawati; Watini, Sri (Jurusan Pendidikan Bahasa dan Seni FKIP Universitas Pattimura, 2024)
This study examines the implementation of an intrinsic reward model, “ASYIK,” in early English education to address low motivation and confidence among young learners in Indonesia. Conventional teacher-centered approaches and reliance on extrinsic rewards often limit engagement and long-term self-motivation in early childhood classrooms. Conducted at TK Kristen Caritas Ambon with 15 children aged 5–6, this qualitative descriptive study employed participatory observation, video documentation, and structured field notes. The ASYIK model was applied through three stages: Motivation (stimulating enthusiasm through rhymes and mini projects on prepositions of place), Action (interactive language practice), and Reward (self-praise in English such as “I can, I’m great, I succeed”). Thematic analysis focused on behavioral and linguistic changes. Findings show that the ASYIK model significantly enhanced children’s confidence, intrinsic motivation, and mastery of prepositions of place in contextual and playful ways. It also fostered positive classroom interactions and socio-emotional growth. The study’s novelty lies in integrating intrinsic self-praise expressions into English learning within a structured Motivation – Action – Reward framework. Theoretically, it contributes to education, language studies, and linguistics by linking intrinsic reward speech acts with character education, linguistic self-regulation, and affective engagement.